Nilai-Nilai Pendidikan dalam Tradisi Haul sebagai Praktik Keagamaan Warga Nahdlatul Ulama di Desa Gedong Kabupaten Semarang - Arif Awaludin (Lakpesdam PCNU Kota Salatiga, 2024)
The haul tradition, as a socio-religious practice of Nahdlatul Ulama communities in Gedong Village, Semarang Regency, contains symbols, social functions, and mechanisms for intergenerational value transmission; however, in the context of social change it may shift into an annual routine that is insufficiently meaningful especially for younger generations thereby weakening its educational force. This article formulates three research questions: (1) what ritual meanings are embedded in the Haul Semangkin ceremony, (2) what socio-cultural functions does the tradition perform for the supporting community, and (3) what educational values are contained within it. Employing a qualitative approach with a phenomenological method to capture residents’ lived experiences and interpretations in a natural setting, data were collected through participant observation, interviews, field notes, and documentation, and were analyzed descriptively through data reduction, categorization, synthesis, and theme development. The findings indicate that Haul Semangkin produces layered symbolic meanings gratitude to Allah SWT, reverence for Ibu Mas Semangkin as an exemplary figure, and the affirmation of filial piety through prayers for the deceased while also performing functions of social integration, social improvement, norm transmission, cultural preservation, and communal entertainment. The dominant educational values comprise: divine values (prayer, gratitude, an orientation toward blessings), social values (mutual cooperation, sharing resources, solidarity), and moral-character values (respect for ancestors and others, orderliness, and responsibility). These findings affirm the haul tradition as a tradition-based “community school” that internalizes values through participation and habituation, while also highlighting the need to strengthen meaning-making and youth engagement so that the tradition does not remain a ritual without value internalization.